Visualization of Eukaryotic DNA Mismatch Repair Reveals Distinct Recognition and Repair Intermediates - Hombauer, Hans (2011)
DNA Mismatch Repair (MMR) increases replication fidelity by eliminating mispaired bases resulting from replication errors. In Saccharomyces cerevisiae mispairs are primarily detected by the Msh2-Msh6 complex and corrected following subsequent recruitment of the Mlh1-Pms1 complex. Here, we visualized functional fluorescent versions of Msh2-Msh6 and Mlh1-Pms1 in living cells. Msh2-Msh6 formed foci in S-phase that colocalized with replication factories; this localized pool accounted for 10–15% of MMR in wild-type cells but was essential for MMR in the absence of the exonuclease Exo1. Mlh1-Pms1 also formed foci that, while requiring Msh2-Msh6 for their formation, rarely colocalized with Msh2-Msh6. Mlh1-Pms1 foci increased when the number of mispaired bases was increased; in contrast, Msh2-Msh6 foci were unaffected. These results suggest that (I) mispair recognition can occur via either a replication factory-targeted or a second distinct pool of Msh2-Msh6, and (II) superstoichiometric Mlh1-Pms1 assembly triggered by mispair-bound Msh2-Msh6 defines sites of active MMR.